Social Factors Affecting Productivity of Integrated Farming: An Experience from Ngantang District, Indonesia - Relawati, Rahayu; Yudi Ariadi, Bambang; Baroh, Istis (International Journal of Engineering and Technology, 2019)
Integrated farming system (IFS) is one of important ways to support sustainable agriculture. There are some important social factors needed to support the success of IFS, beside technical and economical factors. This study aimed to analyze factors of knowledge, attitude, management, and production behavior in affecting productivity of integrated farming. The study was done in Ngantang District, Malang Regency, East Java, Indonesia. Respondents are farmers who applied integrated farming, namely rearing dairy cow, processing biogas and planting crop in one farming system. Data was analyzed by using Structural Equation Modeling (SEM). The result indicates that the strongest influences are obtained between attitude to the production behavior and between management to the productivity of integrated farming, with the influence strength almost double to the others. Next, is the strength of the influence of knowledge to attitude; production behavior to the productivity; management to production behavior. All of them have positive relation. Lastly, the weakness and negative relation is the influence of knowledge on management. It can be inferred from the result that developing positive farmersâ€™ attitudes to the environment and food safety is important to do. Moreover improving management of integrated farming is also important to increase its productivity.Â Â
Keywords: Social factors; integrated farming; SEM; dairy cow; biogas slurry.